NICOLAS ASTRINIDIS (1921-2010): COMPOSITIONAL LANGUAGES IN HIS « ‘ DEUX PIÈCES EN STYLE GREC’ » FOR VIOLIN AND PIANO - Vangelis KARAFILLIDIS (Studia Universitatis Babeş-Bolyai. Musica)
The representatives of the Greek National School followed various stylistic trends according to their background, studies and aesthetical preferences. Thus, elements derived from classicism, romanticism, impressionism or even modernism are utilized in combination with Byzantine and Greek folk music timbre in the entire oeuvre of these composers. The diverse compositional approaches not only revolve around the in principle incompatibilities between all the above mentioned musical entities, but furthermore drastically differ from each other due to the individual ways of handling and balancing the synthesization of aesthetically “diverging” characteristics. Nicolas Astrinidis came in contact with many cultures. He can be characterized as an integrated musician since his artistic skills reached the highest level in piano performing, orchestra conducting and composing. Furthermore, his collaboration as a performer with some of the most important soloists of his generation provided him with a profound knowledge of instrumental techniques. Here, the compositional languages in his ‘Deux Pièces en Style Grec’ for violin and piano (composed in 1947) are analyzed. These pieces illustrate an inventive synthesization of Western music compositional techniques and aesthetic approaches with the Greek folk music timbre.